2014
DOI: 10.3390/s141018625
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Orientation Using Magnetic and Inertial Sensors and Different Sensor Fusion Approaches: Accuracy Assessment in Manual and Locomotion Tasks

Abstract: Magnetic and inertial measurement units are an emerging technology to obtain 3D orientation of body segments in human movement analysis. In this respect, sensor fusion is used to limit the drift errors resulting from the gyroscope data integration by exploiting accelerometer and magnetic aiding sensors. The present study aims at investigating the effectiveness of sensor fusion methods under different experimental conditions. Manual and locomotion tasks, differing in time duration, measurement volume, presence/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
214
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(230 citation statements)
references
References 54 publications
11
214
2
3
Order By: Relevance
“…Accelerometer offset and sensitivity was corrected as described in Reference [29]. Gyroscope offset was removed based on a static measurement before each run [30]. After functional calibration, initial sensor orientation was estimated based on the strapdown and drift-correction algorithm of Reference [31].…”
Section: Inertial Sensorsmentioning
confidence: 99%
“…Accelerometer offset and sensitivity was corrected as described in Reference [29]. Gyroscope offset was removed based on a static measurement before each run [30]. After functional calibration, initial sensor orientation was estimated based on the strapdown and drift-correction algorithm of Reference [31].…”
Section: Inertial Sensorsmentioning
confidence: 99%
“…Medical community applied inertial sensors to evaluate the rehabilitation status and to apply in the health care like fall detection (Alvarez et al, 2016). Many researches about the body link's orientation or angle measurement applied inertial sensors were published (Hu et al, 2014;Cockcroft et al, 2014;Lambrecht and Kirsch, 2014;Slajpah et al, 2014;Bergamini et al, 2015;Chen et al, 2015;Ruffaldi et al, 2015). However, there is no any application in industrial practice was reported.…”
Section: Challengesmentioning
confidence: 99%
“…In this study, we propose to merge both scanning and simultaneous models proposed by Lambrinos et al [15] into a UV-polarized light scanning model providing highly accurate measurement of the heading direction of our walking robot under various meteorological conditions and a low UV-index 1 . Section II presents the UV-polarized light compass.…”
Section: Introductionmentioning
confidence: 99%
“…However local magnetic fields produced by ferrous materials can cause incorrect magnetometer measurements. The classical approaches to magnetic disturbances compensation rely on Kalman filtering and require sensor fusion from gyroscopes and accelerometers [1]. It is well known that gyroscopes and accelerometers are also prone to drifts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation